2019
DOI: 10.31501/rbcm.v27i3.10051
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos Da Mobilização Precoce Em Crianças Com Pneumonia Associada a Ventilação Mecânica: Efeitos Sobre Variáveis Não Lineares Da Variabilidade Da Frequência Cardíaca

Abstract: A pesquisa teve como objetivo verificar os efeitos da mobilização precoce em crianças com pneumonia associada à ventilação mecânica (PAV) sobre variáveis não lineares da variabilidade da frequência cardíaca. Foi realizado um ensaio clínico, prospectivo, de caráter quantitativo realizado em 13 pacientes de ambos os gêneros, com idade média de 3±2,3 anos, com diagnóstico de PAV. O estudo foi aprovado pelo Comitê de Ética e Pesquisa da FSCMP, parecer 2.084.580 e registo no Clinical Trials NCT03343717. A análise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus, it is possible to infer that children submitted to a physical therapy protocol based on physical exercise, which has one of the benefits of increased HRV, both in the post-protocol and in the follow-up, have less susceptibility to events resulting from poor adaptability, in addition to having the benefit of less time in IMV and less time in the ICU 28. The same results of improvement in HRV were found in a clinical trial in children with pneumonia associated with mechanical ventilation 11…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Thus, it is possible to infer that children submitted to a physical therapy protocol based on physical exercise, which has one of the benefits of increased HRV, both in the post-protocol and in the follow-up, have less susceptibility to events resulting from poor adaptability, in addition to having the benefit of less time in IMV and less time in the ICU 28. The same results of improvement in HRV were found in a clinical trial in children with pneumonia associated with mechanical ventilation 11…”
Section: Discussionmentioning
confidence: 76%
“…28 The same results of improvement in HRV were found in a clinical trial in children with pneumonia associated with mechanical ventilation. 11 Other authors have also shown improvements in time on IMV and hospital stay, in addition to functional capacity, increased muscle strength, and decreased late complications 29 in children undergoing early physical exercise. In children, this therapeutic practice is viable and safe, 7 information confirmed by this study since there were no complications such as drops in oxygen saturation or variations in blood pressure that would cause instability to the child.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, it is noted that the variables corresponding to the parasympathetic response (RMSSD and SD1) and the variables corresponding to the global variability of HR (SD2 and SDNN), showed a statistically significant difference between the CG and EG groups, with higher values in the EG. In this sense, in a recent study (Rocha, Santos, Oliveira, Avila, & Rocha, 2019) on the effects of an exercise protocol in children with VAP, higher values were observed in the non-linear HRV variables in the intervention group, demonstrating that performing this conduct can improve the autonomic modulation of HR.…”
Section: Discussionmentioning
confidence: 79%